Security Trade-Off and Energy Efficiency Analysis in Wireless Sensor Networks. (1st June 2015) - Rusinek, Damian; Ksiezopolski, Bogdan; Wierzbicki, Adam
Abstract : With a rapid progress of numerous applications in wireless sensor networks (WSNs), performance evaluation and analysis techniques face new challenges in energy efficiency area in WSN applications. One of the key issues is to perform the security trade-off and energy efficiency analysis. In this paper, the energy analysis module for the QoP-ML (quality of protection modeling language) is proposed by means of which one can analyze the influence of various security levels on the energy consumption of a protocol. Moreover, an advanced communication module is proposed as an extension of the QoP-ML language, which enhances the abilities to analyze complex wireless sensor networks. The case study of WSN deployed on the Jindo Bridge in South Korea was carried out and the lifetime of protocols with various security levels was simulated. The results show that the introduction of various security levels can entail large differences in performance and energy consumption, and hence result in different lifetime. Therefore, the designers of WSN protocols should search for balance between the required lifetime and security level. The introduced QoP-ML extension, along with the AQoPA (automated quality of protection analysis) tool, has been developed to meet the above requirements.